A new serial sampler for collecting gas-tight samples from seafloor cold seeps and hydrothermal vents. (July 2020) - Wang, Shuo; Wu, Shijun; Du, Mengran; Yang, Canjun; Wang, Xun
Abstract: This paper details the development and application of a new serial sampler capable of acquiring multiple deep-sea gas-tight fluid samples. It consists of a custom-made multiport sampling valve with six sampling cylinders distributed around it in a circle. The serial sampler can operate on the seabed to depths of 7000 m. Each cylinder has a sampling volume of about 160 ml and can maintain the sample at near in-situ pressure. It can be deployed by HOV or ROV to collect gas-tight fluid samples via remote or automatic operation. The new serial sampler was successfully field-tested at cold seep sites in the Gulf of Mexico and the South China Sea and also at hydrothermal vent sites on the Juan de Fuca Ridge and in the Indian Ocean. Highlights: The sampler could be deployed at seafloor to automatically collect time series gas-tight fluid samples. A unique multiport sampling valve allows fluid to enter any one of the six titanium bottles of the sampler. A flushing pump is integrated into the sampler to reduce the influence of the dead zone volume.